Local Air Quality and Noise Assessment for Landing and Take-Off Operations in Future Airport Environment - Danlin Zheng Zhang; Daniel Gómez López; Juan Antonio López Sánchez; Chen Xia; Xin Wang; Alba García Fernández (Engineering Proceedings)
This study examines improvements in local air quality and noise (LAQ&N) of the Landing and Take-Off cycle (LTO cycle) with the introduction of a hybrid electric/sustainable mid-range aircraft. Using Dortmund Airport as a case study, the results highlight significant environmental benefits. Future traffic scenarios estimate potential gains: INDIGO flights improve LAQ by up to 74% and noise impacts by 36%. When replacing 15% of the future traffic demand with INDIGO aircraft, up to a 3% benefit in LAQ&N can be expected. Full traffic replacement scenarios promise substantial environmental advantages, affirming the INDIGO aircrafts’ role in greener aviation.